Horticultural species of the island of Lokrum in the period of archduke Maximilian of Habsburg (1859-1869) and their current state : Hortikulturne vrste lokrumskih vrtova u periodu nadvojvode Maksimilijana Habsburškog (1859.-1869.) i njihovo sadašnje stanje - Marić, Mara (Array, 2020)
This research, conducted within the ornamental gardens of the Island of Lokrum and based on the original archival documents from Trieste State Archives (AST) and Austrian State Archives (OeStA) in Vienna, was aimed at creating the first unique list of horticultural plant taxon planted on the island during the reign of the Archduke Ferdinand Maximilian Habsburg (1859-69). The research identified 213 taxa, including 184 species, 4 varieties, 8 hybrids and 17 cultivars. There were 193 allochthonous taxa, mostly originating from Central and South America (66), including 47 Asian species, 21 Australian species, 17 African species and 13 South American species. The Archive lists 20 taxa autochthonous in Croatia. While the number of the autochthonous taxa had apparently been higher, the historical documents have mostly recorded only the introduction of exotics. At that time, the following taxa were for the first time introduced in this part of the Adriatic, on the Island of Lokrum: Ananas comosus, Musa x paradisiaca, M. acuminata, Eucalyptus diversifolia, E. globulus, Araucaria araucana, A. columnaris, A. angustifolia, A. bidwillii, A. cunninghamii, Bougainvillea spectabilis and Citrus reticulata. At the location of the ornamental gardens, 51 ornamental allochthonous taxa and 20 autochthonous taxa were identified today. Within this number, only 21 allochthonous taxa and 9 autochthonous taxa remain present since the period of Maximilian. According to the 2018-2019 inventory, 71 taxa have been inventoried within the ornamental gardens on Lokrum, belonging to 43 families and 64 genera. Due to lack of intensive maintenance of the gardens, the majority of allochthonous, exotic species failed to survive within the autochthonous island vegetation. The list of taxa from Maximilian’s gardens presented in this paper and retrieved from the archival sources, will be the starting point of the restoration process that awaits these gardens.